Providing Education and Welfare Opportunities for Syrian Children Near Conflict Zone - Pinar Burcu Guner (Ethics in Progress, 2020)
The article aims to 1) focus on welfare opportunities near the conflictzone in Turkey. Providing a good life for children under every condition belongs tothe responsibilities of both, national and international communities. The CapabilityApproach Theory seems to promote such responsibilities at best. However, theTurkish example does not show effects as satisfactory as the German examplewith Turkish migrant children, which is discussed in this article and illustratedwith research findings provided by the author.